Traditional plant based therapy among rural communities of some villages of Baramulla district (Jammu and Kashmir) - Yousuf, Javaid; Verma, Raj Kumar; Dar, Hamidullah (Journal of Phytology, 2013)
The medicinal properties of plant species have made an outstanding contribution in the origin and evolution of many traditional herbal therapies. Keeping this thing in view, an ethno medicinal survey was carried out to study traditionally used plants by the rural communities of Baramulla district Jammu and Kashmir. It was found that due to poor condition of modern healthcare facilities and poverty, people of the area fully or partially rely on local medicinal plants for curing diseases. The study documented 32 plant species belonging to 22 families. Lamiaceae was the most represented plant family (5 species). Among the documented plant species 23 were herbs, 4 shrubs, 3 trees and 1 climber. The study revealed that the mostly used plant parts for therapeutic purposes were leaves followed by roots. During the course of study it was observed that most of the diseases treated were cough, rheumatism, fever and urinary disorders. It was found that the study area is fairly rich not only in medicinal wealth but also have deeply rooted traditional knowledge hence scientific investigations are desirable to validate their claims.